Herring Fishing. - Fagan, George, 1879-1907.; Holloway, Joseph, 1861-1944 (1902)
Black and white illustration on card with caption "Herring Fishing" written very faintly in pencil in manuscript hand underneath and signed and dated by the artist "Ua Fágáin" at lower right within the illustration. Illustration depicts a boat with its' sail up in cloudy, bracing weather; two seagulls are depicted in flight in the foreground. In the left background, an outcrop of land and the mast of another large boat can be seen. [The artist George Fagan also often signed his name "Ua Fágáin" and 'S. Uí Fhágáin'].
Keywords: Boats -- Ireland -- 1900-1910.; Herring fishing -- Ireland -- 1900-1910.; Gulls -- Ireland -- 1900-1910.; Ink drawings -- Irish -- 1900-1910; Pen works -- Irish -- 1900-1910